2005
DOI: 10.1007/s11274-005-2303-z
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Bt Toxin in the Rhizosphere of Transgenic Bt Cotton and its Influence on Soil Functional Bacteria

Abstract: The concentrations of Bacillus thuringensis (Bt) toxin released from root exudation of Bt cotton were measured by an enzyme-linked immunosorbent assay (ELISA), and its impacts on the numbers of culturable functional bacteria in the rhizosphere were determined by cultivation. No Bt toxin was found in the rhizosphere of non-Bt cotton (SHIYUAN321), but varying levels of Bt toxin were present in the rhizosphere of two Bt cotton varieties (NuCOTN99 B and SGK321) during the entire growth period. The levels of Bt tox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 24 publications
5
43
0
1
Order By: Relevance
“…For example, USEPA (2001) proposed no effect of Bt cotton on numbers of Collembolan, Folsomia candida. Rui et al (2005) reported no effect on culturable functional bacteria. Shen et al (2006) revealed no any direct adverse effect of cultivation of transgenic Bt cotton on functional bacteria populations or functional diversity of microbial communities in the rhizosphere soil.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, USEPA (2001) proposed no effect of Bt cotton on numbers of Collembolan, Folsomia candida. Rui et al (2005) reported no effect on culturable functional bacteria. Shen et al (2006) revealed no any direct adverse effect of cultivation of transgenic Bt cotton on functional bacteria populations or functional diversity of microbial communities in the rhizosphere soil.…”
Section: Discussionmentioning
confidence: 97%
“…Once released in soil, Bt toxin get adsorbed or bound on clay particles, humic components, or organic mineral complexes and in this way is protected against degradation by soil microorganisms (Tapp et al, 1995). Therefore, repeated cultivation of Bt cotton on same location might affect the composition and activity of soil microbial communities (Donegan and Seidler, 1999;Rui et al, 2005) and the soil biochemical 1999; Ekschimitt et al, 2001;Verschoor et al, 2001), and have been regarded as sensitive indicators of the stress caused by ecological disturbance and soil pollutants in natural ecosystems (Sochová et al, 2006). Simultaneously, soil nematodes are susceptible to the toxin from B. thuringiensis (Bottjer et al, 1985;Meadows et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Few or no effects of Bt plants expressing Cry proteins were found on nontarget invertebrates in soil, such as earthworms [81,85,173], collembolans [173][174][175][176][177], isopods [178][179][180], mites [177,181], nematodes [81,182], and snails [183,184]. In contrast, several studies have indicated that Bt plants affect microbial communities [185][186][187], the activities of some enzymes [167,168,188], and some microbe-mediated processes and functions in soil [169,185,189].…”
Section: In Situ Field Studies Of Microbial Populations and Enzyme Acmentioning
confidence: 99%
“…Wu et al [167,168] found that decomposing straw of Bt rice containing the Cry1Ab protein was not toxic under laboratory conditions to a variety of culturable microorganisms in a flooded paddy soil. Rui et al [186] found lower numbers of culturable functional bacteria (potassium-dissolving bacteria, inorganic phosphatedissolving bacteria, and nitrogen-fixing bacteria) in the rhizosphere of Bt cotton than of near-isogenic non-Bt cotton only during the early and middle growth stages but not after the growing season. Shen et al [166] reported that the functional diversity of microbial communities was not different in rhizosphere soils of Bt and non-Bt cotton.…”
Section: In Situ Field Studies Of Microbial Populations and Enzyme Acmentioning
confidence: 99%
“…Molecular analysis of the bacterial community also showed no significant impact on the dominant members of the bacterial community and soil protease activity was not inhibited by the release of constitutively over-expressed protease inhibitor (Riglietti et al, 2008). No significant harmfu impact on CFUs of bacteria, actinomycetes and fungus between the Bt and non-Bt cotton rhizosphere during cropping season at one particular stage (Zwahlen et al, 2007;Zaman et al, 2015),even at far higher concentration of the Bt proteins , no recombination event was detected between plant DNA and soil bacteria (Velasco et al, 2013), but other factors may be involved (Rui et al, 2005) and more studies are needed to assess the impact of the continuous release of Cry1Ab via root exudates and plant biomass on the soil ecosystem (Zwahlen et al, 2007).…”
Section: Introductionmentioning
confidence: 98%